Using Facebook Comments in Teaching Writing Skill - Pungky Ramadhani (International Consortium of Education and Culture Research Studies, 2018)
In learning a language, writing is considered as the most difficult skill to be mastered by the students. They should pay attention on the writing components to produce a good writing. This becomes a challenge for the teachers. The teachers should create a new atmosphere of teaching writing. In this case, the existence of media is needed. Facebook was found to be the most popular social media site used by students. There a lot of features provided by Facebook. One of the features is Facebook comments. In this research, the researcher will use Facebook comments in Facebook group as the media to teach writing skill.